2015
DOI: 10.4103/2394-4722.158803
|View full text |Cite
|
Sign up to set email alerts
|

Role of circulating tumor cells in future diagnosis and therapy of cancer

Abstract: Circulating tumor cells (CTCs) have become a blistering topic of discussion for oncologists because of their tremendous potential in the diagnosis and treatment of cancer. Over the past few years, they have been doled with quite an amount of research in this area understanding that CTCs are shed from tumors and circulate in the bloodstream. This process can also occur at an early stage of cancer. The major limitation in isolation of CTCs is their availability in limited numbers. Hence, many techniques have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 110 publications
1
49
0
Order By: Relevance
“…[24] CTCs are shed by primary tumors into the vasculature and circulate in the blood of cancer patients; [25] however, they are not easily identified, due to their very limited numbers. Pantel et al [26] reviewed the importance of CTCs, including the biological properties of metastatic cells involved in cancer progression, and stated that CTC-derived cell lines could be used to develop new therapeutic targets, and for drug screening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24] CTCs are shed by primary tumors into the vasculature and circulate in the blood of cancer patients; [25] however, they are not easily identified, due to their very limited numbers. Pantel et al [26] reviewed the importance of CTCs, including the biological properties of metastatic cells involved in cancer progression, and stated that CTC-derived cell lines could be used to develop new therapeutic targets, and for drug screening.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have described the development of in vivo and in vitro methods for the isolation of CTCs in larger numbers from metastatic cancer patients, for use in research into the role of CTCs in cancer progression, [27][28][29] and with the aim of targeting such cells to cure cancer; hence CTCs are a topic of intense discussion among oncologists. [25] Many techniques have been developed and are under continuous improvement to enhance the efficacy of CTC isolation and enumeration. [16] Comparison of the OncoQuick density gradient method with FicollHypaque density gradients for separation of tumor cells from bone marrow and peripheral blood aspirates indicated that CTCs can be easily aspirated by both methods and analyzed further to determine their presence and quantity.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular profiling of CTCs is therefore an integral part of CTCs analysis and provides accurate phenotypes of these cancer cells. [6] So far it is well established that certain genes are upregulated, downregulated or mutated in several solid tumor malignancies and their analysis can help in proposing targeted therapies to treat many of these cancers. A major phenomenon seen in CTCs in metastatic cancer is their transformation during EMT transition.…”
Section: Molecular Profiling Of Ctcsmentioning
confidence: 99%
“…The major reason for this is the extremely small number (6)(7)(8)(9)(10) of CTCs in the bloodstream, and their heterogeneity affecting their cell surface markers in isolation. However, tissue biopsies have limited effectiveness as a diagnostic tool because they are invasive and not suited to repeated sampling; biopsies also cannot monitor the treatment of metastatic cancer patients during therapy.…”
mentioning
confidence: 99%
“…[1] Thus, the opportunity to obtain essential information from blood samples, as so-called liquid biopsies, would offer significant advantages.Noninvasive detection and monitoring of patient tumors, employing cell-free circulating tumor DNA (ctDNA) or circulating tumor cells (CTCs), have been employed for investigations into multiple tumor types. [2][3][4] CTCs are described as cells, shed by primary or secondary tumors into vasculature, that keep circulating in the bloodstream of cancer patients. [5] Reports indicate that patients with lower counts of CTCs survive longer than the patients with higher CTCs counts.…”
Section: Introductionmentioning
confidence: 99%